Pozorne czy autentyczne? Trwałe czy możliwe? Piękno sztuki współczesnej w koncepcjach Hansa G. Gadamera i Odo Marquarda - Kazimierska-Jerzyk, Wioletta (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2006)
Contemporary aesthetics, reaching the remotest limits of theory in its determined endeavours to embrace new artistic phenomena, often questions the very idea of beauty. According to Christian Enzensberger, however, all attempts at such questioning are doomed to failure. Beauty, as he claims, seems to be timeless. Still, beauty in contemporary art has its faults and, among others, it is accused of being something else that it purports to be. There is ample evidence to support this view: comparisons between the illusory beauty with rich terminology borrowed from aesthetic pluralism; failed attempts at redefining beauty, its false comebacks under the guise of plagiarism and quotations, and, finally, it is more than obvious that beauty is being confused with other phenomena, not necessarily of aesthetic or artistic nature. Writers who would be able to persuasively combine the philosophy of beauty with modern and contemporary art are in great scarcity. Hans G. Gadamer and Odo Marquard can be counted as the rare exceptions. They refrain from offering subjective redefinitions of beauty, but instead they re-evaluate the concept of beauty in keeping with the tradition of aesthetics.